A UTILIZAÇÃO DO BIM NO PROCESSO DE PROJETO DA CONSTRUÇÃO CIVIL: UM ESTUDO DE CASO DE NOVE ESCRITÓRIOS BRASILEIROS DA NOVA GERAÇÃO - Stumpp, Monika Maria; Braga, Gisele Pinna; Bertoli, Gabriela Mann; Christ, Ana Karina de Barros (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Once the BIM platform has been used by Brazilian architectural offices, how to evaluate their knowledge about its use and potential? Considering such questions this article is part of a research in progress that investigates the published works by offices that stood out in the field of architecture. Five renowned professors and architecture critics elected 25 young offices that would be part of the new generation of Brazilian architecture. This paper investigates the use of the BIM platform in nine offices of that group. The results expose what contemporary Brazilian offices say about their use of BIM platform. Although the sample seems small, it is representative, because this universe is still restricted in the Brazilian market.